2013
DOI: 10.3109/10826084.2013.828753
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ Knowledge About Smoking-Related Health Problems in Lebanon

Abstract: The relationship between smokers' knowledge about smoking related health problems and the motivation to quit smoking in a sample of Lebanese smokers was evaluated. The first group of smokers was composed of hospitalized subjects for a cardiologic or a respiratory health problem (n = 42). The second group was composed of smokers who have not suffered from any smoking-related health problem (n = 69). A positive correlation was found between the Richmond test score and the knowledge level about smoking related he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Evidence shows that tobacco smoking depends on complex social-structural processes ( 22 ) and hence, behavior modification theories are needed for effective WTS prevention ( 23 ). Previous studies into cigarette smoking reported that most smokers were unaware of smoking-associated risks such as mouth cancer, lung diseases, and myocardial infarction ( 24 , 25 ). However, there are limited studies into knowledge, attitude, and BI among waterpipe tobacco smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that tobacco smoking depends on complex social-structural processes ( 22 ) and hence, behavior modification theories are needed for effective WTS prevention ( 23 ). Previous studies into cigarette smoking reported that most smokers were unaware of smoking-associated risks such as mouth cancer, lung diseases, and myocardial infarction ( 24 , 25 ). However, there are limited studies into knowledge, attitude, and BI among waterpipe tobacco smokers.…”
Section: Introductionmentioning
confidence: 99%